TEKS DAN DISKURSUS OTORITAS MENURUT KHALED M. ABOU EL-FADL - Muhammad Fahmi Hidayatullah; Firmanda Taufiq (Risalah, Jurnal Pendidikan dan Studi Islam, 2021)
In it contains authoritative references in religious matters. Meanwhile, in Khaled's view, Islamic jurists are a source of legitimacy in interpreting religious texts. Khaled tried to criticize the construction of authoritarianism in Islamic law, especially regarding the criticism of the misogynistic fatwas issued by the Council for Scientific Research and Legal Opinion (CRLO) and The Society for Adherence to the Sunnah (SAS). In this article, this article analyzes and examines how Khaled M. Abou El-Fadl's ideas offer in matters of text and discourse of authority in Islamic studies, especially those related to the interpretation of religious texts, namely the Al-Quran and hadith. While the method used in this research is a qualitative method using a descriptive-analysis approach. From various facts and data obtained, then analyzed and narrated descriptively with reference to the focus of this study. Based on the research findings, it was found that religious texts should be able to be translated and read properly according to their context, especially the authority and authoritarianism inherent in Islamic studies.